Effects of high-intensity intermittent training on some inflammatory and muscle damage indices in overweight middle-aged men - Behnam Rohnejad; Amirabbas Monazzami (Elsevier, 2023)
Introduction: Recently, the use of various high-intensity intermittent training (HIIT) that have quick recovery periods are of great importance. Therefore, the purpose of this research was to investigate the acute effect of HIIT training on the serum levels of inflammatory and muscle damage indices in overweight middle-aged men, as well as the kinetics of these markers at 1, 24, and 48 h after HIIT training. Methods: Twenty-two middle-aged men (40-60 years, BMI 25-30 kg/m2) were divided into two training (n=12) and control (n=10) groups. The HIIT training program consisted of running on treadmill for 30 s with an intensity of 100% maximum aerobic speed (MAV), 30 s active recovery with 50% aerobic speed (4 sets, 4 repetitions and 5 min of rest between each round). Cortisol, IL-6, CRP, ALT, AST, CPK and LDH were evaluated in pre-test, one- hour, 24 and 48 h after HIIT training. Results: Except for the CRP variable, Cortisol, IL-6, CPK, LDH, ALT and AST had a significant increase in one- hour after HIIT compared to the pre-test (P<0.05). Also, IL-6 and CPK variables had a significant increase in 24 h and only CPK had a significant increase in 48 h after HIIT training compared to pre-test (P<0.05). Conclusion: Overall, due to long rest intervals and low activity time during HIIT, inflammatory responses and muscle damage are not severe. The recovery periods of inflammatory and muscle damage markers are faster, so this type of response can be considered an advantage for overweight middle-aged men.